Experimental determination of the effective point of measurement for cylindrical ionization chambers in 60Co gamma radiation - Legrand, Carine; Hartmann, Günther H.; Karger, Christian (Physics in medicine and biology, 2012)
The displacement effect of cylindrical ionization chambers is taken into account either by an effective point of measurement (EPOM) or, alternatively, by using a displacement perturbation factor. The dependence of these effects in water was examined as a function of the cavity radius using cylindrical chambers with different radii and a plane-parallel chamber, whose EPOM is well known. Depth-dose curves were measured in terms of absolute absorbed dose in water and evaluated according to the international protocol IAEA TRS-398 as well as the German protocol DIN 6800-2. As expected, evaluation of absorbed dose under reference conditions following both protocols agreed well within a standard uncertainty of 0.1%. However, values of absorbed dose at depths beyond the dose maximum showed deviations up to 0.3% and 0.5% for IAEA TRS-398 and DIN 6800-2, respectively. Values in the build-up and maximum region did not agree very well. Deviations of more than 1% were found for both protocols. It was concluded that the corrections recommended in both protocols are not fully appropriate. A procedure is suggested to measure the absorbed depth-dose distribution including the build-up region with an improved accuracy by means of cylindrical chambers.
Im Titel ist die Zahl "60" hochgestellt
Gesehen am 17.01.2022